Improving mental health by improving the mental health literacy? Study protocol for a randomised controlled evaluation of an e-mental health application as a preventive intervention for adolescents and young adults - Krokos, Olivia; Brandhorst, Isabel; Seizer, Lennart; Gawrilow, Caterina; Löchner, Johanna (Internet Interventions, 2024)
Background: From the age of 14, many adolescents enter a vulnerable developmental phase, with a sharp increase in mental illness at 16. The COVID19 pandemic has further exacerbated this issue. Hence, universal and easily accessible prevention in the young is needed. E-mental health interventions are on the rise due to numerous benefits such as potential low-costs, low-threshold and high scalability. However, effectiveness and acceptance of mobile health (mHealth) preventive interventions remain unresearched. Method: In a two-armed, randomised controlled study design adolescents and young adults from 14 years old will be recruited. Following an initial baseline assessment, they will be randomised to a) the intervention group (IG, n = 75), which will receive a mHealth intervention (the application ‘Mental Health Guide’, co-developed by lived experience experts) or b) the waiting list control group (CG, n = 75). Both groups will be followed up after 3 and 6 months following post assessment. We hypothesize an increase in mental health literacy in the IG compared to the CG for post and follow-up assessment (primary outcome: Mental Health Literacy Scale). In addition, we expect an improvement in mental health and psychological well-being, improved emotion regulation, reduced psychological distress, as well as good quality ratings in usability and acceptance in the use of the ‘Mental Health Guide’ We performed multiple simulations of possible outcome scenarios, incorporating an array of factors, to generate realistic datasets and obtain accurate estimates of statistical power. Conclusion: As a first-of-its-kind in this field, this study investigates whether a mHealth intervention based on mental health literacy may improve the mental health literacy and further aspects of psychological functioning of young people in a vulnerable phase. Furthermore, the results promise to provide important knowledge of how universal prevention may be implemented with low costs for diverse populations. Trial registration: This trial was registered in the DRKS register (DRKS-ID: DRKS00031810) on 23 June 2023.
CRIS-Team Scopus Importer:2024-11-26
Keywords: Adolescence; Mental health literacy; mHealth; Prevention